Front Cover Picture: Stereoselective Cyclopropanation of Boron Dipyrromethene (BODIPY) Derivatives by an Organocascade Reaction (Adv. Synth. Catal. 5/2022). Issue 5 (31st January 2022) - Dočekal, V.; Koberová, T.; Hrabovský, J.; Vopálenská, A.; Gyepes, R.; Císařová, I.; Rios, R.; Veselý, J.
Abstract : The front cover picture illustrates the stereoselective synthesis of BODIPY molecules, in connection to the stereo audio player with the inscription "stereo bodipy." The BODIPY molecule is inserted by a robot symbolizing the simplicity of preparation of such molecules. The synthesis of enantiopure chiral BODIPY molecules is of importance due to their intrinsic properties as fluorophores that could be used as probes for molecular sensing. The cover image was created by Tomáš Belloň. Details can be found in the Research Article by Veselý and co‐workers (V. Dočekal, T. Koberová, J. Hrabovský, A. Vopálenská, R. Gyepes, I. Císařová, R. Rios, J. Veselý, Adv. Synth. Catal . 2022, 364, 930–937; DOI: 10.1002/adsc.202101286 ).